THE EFFECT OF POPULATION SIZE, EDUCATION LEVEL, AND ECONOMIC GROWTH ON POVERTY IN DISTRICT/CITIES IN ACEH PROVINCE - Hawadayanti, Nur; Ratna, Ratna; Nailufar, Fanny; Juanda, Reza (LPPM Universitas Malikussaleh, 2025)
This study aims to examine the influence of population size, education level, and economic growth on poverty in regencies/municipalities within the Aceh Province. The research employs a combination of cross-sectional and time series data from 23 regencies/municipalities in Aceh Province during the period 2019–2023. Data analysis was conducted using panel data regression with the assistance of Eviews software. Based on the analysis, the selected model is the Random Effects Model (REM), which indicates that, partially, both population size and education level have a negative and significant effect on poverty in the regencies/municipalities of Aceh Province. In contrast, economic growth has a positive but statistically insignificant effect. Simultaneously, population size, education level, and economic growth are found to have a positive and significant effect on poverty in the regencies/municipalities of Aceh Province.